Law Enforcement in Efforts to Prevent Doping Use at PON XXI Aceh-North Sumatra - Pratama, Rivan Saghita; Segara Hutabarat, Iqbal Tama (UNIVERSITAS NEGERI MAKASSAR, 2024)
The use of doping is an instant way to improve performance and achieve achievements, but it endangers the body's condition. This research aims to describe anti-doping regulations, efforts made by related parties in enforcing the law on doping use at the XXI Aceh-North Sumatra PON 2024, enforcing this law, as well as challenges and emphasis in preventing and monitoring doping. The research method is qualitative research through data collection using library research and then describing it. The results of the research identified that regulations prohibiting the use of doping refer to anti-doping rules by the Indonesia Anti-Doping Organization (IADO), Code documents by the World Anti-Doping Agency (WADA), and related laws, related to the prevention and control of doping in XXI Aceh PON sports. -In North Sumatra in 2024, various efforts and policies have been carried out by the National Sports Committee (KONI), the Indonesian Anti-Doping Organization (IADO and other interested parties. As a result, not a single athlete was proven to have violated anti-doping -doping rules through sample testing. However, in general, Nationally, there are challenges in implementation efforts that need to be considered and solutions sought.